Supervisor support and virtual leadership moderate the association between technostress creators and strain in remote work: Evidence based on hair cortisol and occupational physician’s hetero-evaluations - Damiano Girardi; Sebastiano Rapisarda; Elvira Arcucci; Laura Dal Corso; René Riedl; Isabella Pividori; Alessandra Falco (PLoS ONE, 2025)
We investigated the association between technostress creators (TCs) and the strain response among smart workers, who are defined as individuals who make extensive use of information and communication technologies for work-related tasks and in interpersonal relationships with colleagues and supervisors. The moderating role of supervisor support and virtual leadership was a specific focus of our study. We conducted two studies, in each of which we complemented the self-report measures on the TCs and supervisor support and virtual leadership with more objective measures of stress and strain. In Study 1, we investigated the association between perceived TCs and hair cortisol concentration (HCC) as a biomarker of stress. In Study 2, we examined the association between perceived TCs and stress-related psychophysical symptoms (i.e., psychophysical strain) as assessed by the occupational physician (i.e., hetero-evaluation). In Study 1, 102 smart workers from different organizations completed a self-report questionnaire and we collected a strand of hair. Study 1 provided little support for the association between TCs and HCC, but supervisor support did affect the association between techno-uncertainty (one of five TCs) and HCC, which was positive when support was low, but negative—albeit marginally significant—when support was high. In Study 2, 105 smart workers from a company in the service sector completed a self-report questionnaire and underwent an occupational health examination. Techno-invasion (another TC) was positively related to psychophysical strain as assessed by the occupational physician. In addition, virtual leadership attenuated the association between three TCs (techno-overload, techno-invasion, techno-insecurity) and psychophysical strain. Based on these nuanced pattern of results, our studies suggest that TCs lead to a strain response among smart workers, and that positive relationships with one’s supervisor—in terms of supervisor support and virtual leadership—can attenuate the negative consequences of technostress.